The philosopher's happiness in Plato's "Republic" - Emond, Ben (University of Ottawa (Canada), 2006)
In this thesis, I argue for the position that happiness is a communal concept in Plato's Republic. By a communal concept, I mean that one must act for the sake of one's community in order to be happy. I make this argument by contending that justice, a notion which involves the consideration of others, is the key to making an individual happy. I argue that Plato has both an altruistic and egoistic concept of justice, and that the interplay between these two concepts of justice constitutes Plato's concept of happiness in the Republic. What results is a kind of happiness which is associated with internal goods, such as having a well-balanced soul, as opposed to the idea of happiness being related to the acquisition of external goods like wealth.
Keywords: Philosophy.